PENDEKATAN UNIVERSAL DESIGN FOR LEARNING (UDL) DALAM PENDIDIKAN INKLUSI: TINJAUAN SISTEMATIS LITERATUR - Fadilah; Dewi Lestari; Nurfitra; Muh. Farid Nur; Nurhasanah; Diarti Andra Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of the Universal Design for Learning (UDL) approach in inclusive education to address the diverse needs of learners. This approach focuses on providing flexible ways of delivering learning materials, encouraging student engagement, and offering various forms for expressing learning outcomes. As a review, the Universal Design for Learning (UDL) approach in inclusive classrooms can improve learning accessibility, increase student engagement, and promote higher academic achievement. The success of its implementation is influenced by several elements, such as teachers’ professional competence, school support, and the use of educational technology. Nevertheless, a number of obstacles are still found, especially in terms of limited facilities and insufficient teacher readiness. Therefore, continuous improvement is needed so that this approach can be maximized in creating a more inclusive and equitable learning environment.